The Effectiveness of Living Things with The Environment Teaching Materials as A Supplement to Improve Scientific Literacy of Junior High School Students - Alimah, Alimah; Endang Susilowati, Sri Mulyani; Subekti, Niken (Journal of Innovative Science Education, 2021)
The ideal science learning reflects the domain of balanced scientific literacy. Student who has scientific literacy are able to master science content, understand the characteristics of science and be able to recognize the environment through scientific process and apply science concepts in real life. Based on that statement we developed a research-based teaching material. This study aims to analyze the effectiveness and appropriateness of teaching materials about Interaction of Living Things with the Environment for grade VII. The research method was used Research and Development teaching materials. Data taken in the form of module eligibility was validated by the media and material experts. Teaching materials effectiveness was analyzed by posttest score, teaching materials characteristics was described by the percentage of teaching materials characteristics based on scientific literacy. The results showed that the science teaching materials have developed was valid, feasible, and effective to support Interaction of Living Things Learning. It have characteristics based on scientific literacy and equipped with pictures to clarify the practicum process, completed with observation tables as testing data that could guide students to find the concepts being taught.